1992
DOI: 10.1038/ng1092-153
|View full text |Cite
|
Sign up to set email alerts
|

Missense glucokinase mutation in maturity–onset diabetes of the young and mutation screening in late–onset diabetes

Abstract: We describe a codon 299 mutation in the glucokinase gene in a British pedigree with maturity-onset diabetes of the young (MODY) resulting in a substitution of glycine to arginine. One out of fifty patients diagnosed with classical late-onset type 2 diabetes mellitus was also found to have this mutation. All nine relatives of this patient who have inherited the mutation have type 2 diabetes, although six others without the mutation are also present with diabetes. The discovery that glucokinase mutations can cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 17 publications
3
82
1
1
Order By: Relevance
“…2). They have been found in subjects of many different racial and ethnic backgrounds including Caucasians (Brazil [this report], France [4,10,11], Italy [20], Sweden [21], Switzerland [22], United Kingdom [23], and United States [24] ), Asians (Japan [15,16,25] ), blacks (Congo [11] ), and admixed populations (African-American [21,26] and Puerto Rican [24] ). The majority of the mutations identified to date have been described in only a single family suggesting that the present list is not exhaustive and that new mutations will continue to be found.…”
Section: Discussionmentioning
confidence: 99%
“…2). They have been found in subjects of many different racial and ethnic backgrounds including Caucasians (Brazil [this report], France [4,10,11], Italy [20], Sweden [21], Switzerland [22], United Kingdom [23], and United States [24] ), Asians (Japan [15,16,25] ), blacks (Congo [11] ), and admixed populations (African-American [21,26] and Puerto Rican [24] ). The majority of the mutations identified to date have been described in only a single family suggesting that the present list is not exhaustive and that new mutations will continue to be found.…”
Section: Discussionmentioning
confidence: 99%
“…Population association studies of the GK gene locus between normoglycaemic and Type 2 diabetic American Blacks [72] and Mauritian Creoles [73] have been positive. Mutations have now been recorded in some families with MODY (Type 2 diabetes subtype presenting from the second decade with an autosomal dominant mode of inheritence) [41, [74][75][76]) and in one pedigree thought to have classic Type 2 diabetes [77] but no other mutations have yet been identified in the common variety of the disease.…”
Section: Glucokinase and Candidate Genes For Type 2 Diabetesmentioning
confidence: 99%
“…In the French study a nonsense mutation in exon 7 of the GK gene was identified [GAG (Glu) to TAG (amber termination codon)] [75] together with two further missense mutations in exon 7 (Thr-228--->Met and Gly-261--+Arg) that cosegregate with diabetes [41]. In the UK study a missense mutation in exon 8 was identified (Gly-299--->Arg) [77]. Molecular modelling studies suggest that mutation of Thr-228 may affect GK affinity for ATP and that Gly-261 mutation may affect glucose binding i.e.…”
Section: Glucokinase Gene Mutations In Type 2 Diabetesmentioning
confidence: 99%
“…Several nonsense and missense mutations have recently been identified in the GCK gene as a cause of hyperglycemia in MODY (6,7,9) and in a few late-onset NIDDM families (8,24). We here report a deletion in the 5' splice site of intron 4 in the GCK gene that is responsible for diabetes in a French MODY family.…”
Section: Discussionmentioning
confidence: 78%
“…16 different nonsense and missense mutations in the glucokinase gene have been identified in affected members ofthese MODY families (6)(7)(8)(9). These mutations were shown to impair the enzymatic activity of the encoded protein (10).…”
Section: Introductionmentioning
confidence: 99%